FACTORS AFFECTING THE SUCCESS OF EXCLUSIVE BREASTFEEDING AMONG BREASTFEEDING MOTHERS IN CHILD’S POLY OF DKT GUBENG POJOK HOSPITAL, SURABAYA - Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Mahfudh Jamil (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Background. The survival of children to grow and develop and get good care is needed to achieve a healthy generation. The success of exclusive breastfeeding in infants 0-6 months in Indonesia still does not meet expectations due to a poor knowledge of the importance Exclusive Breastfeeding and their perception of infant formula is better than breast milk. The low achievement of breastfeeding (ASI) exclusively due to several factors, namely low knowledge of the mother of the importance of breastfeeding, the sex of the baby, birth weight or premature birth, culture that does not support, families that do not support, and social change that happening in the community.Objective. This study aimed to examine predictive factors toward the success of exclusive breastfeeding among breastfeeding mothers in Child’s Poly DKT Gubeng Pojok Hospital, Surabaya.Methods. The design of this study is a cross-sectional study. The variables studied were age, occupation, level of education, family support, and exclusive breastfeeding success. The results of this study were analyzed using the Stepwise Multiple Regression method with SPSS 21.Result. Family support (β = 0.78, p < .001) were significant predictor of exclusive breastfeeding success and accounted 75.9% in the variance of exclusive breastfeeding success (R2 = .759, F (4, 27) = 9.18, p < .001).Conclusion. The importance of family support in supporting the success of exclusive breastfeeding in infants 0-6 months. For this reason, health workers are expected to improve their approach to families so that they want to provide support to breastfeeding mothers. Keywords: Exclusive breastfeeding, infants 0-6 months, factors affecting, breastfeeding mothers